Preparation, Characterisation And Adsorption Properties Of Chitosan And Chitosan Derivatives Beads For The Removal Of Copper(Ii) And Lead(Ii) Ions - Fatinathan, Sharon (2010)

(untitled)
In this study, a batch adsorption system was applied to study the adsorption of copper(II) and lead(II) ions onto chitosan, chitosan-glutaraldehyde (GLA) (1:1 and 1:2), chitosan-alginate and chitosan-tripolyphosphate (TPP) beads. The physicochemical properties of all five adsorbents were analysed based on infrared spectroscopy, light metal cations analysis, surface area and pore size analysis, CHN analysis and X-ray diffraction analysis. Different parameters affecting the adsorption capacity such as initial pH, agitation period, agitation rate, particle sizes, adsorbent dosage, initial concentration of metal ions and temperature were studied. Adsorption isotherm data for copper(II) and lead(II) ions onto all five adsorbents were determined and correlated with Langmuir, Freundlich, Dubinin-Radushkevich (D-R), Sips and Redlich-Peterson (R-P) isotherm models.